Techno-economic Analysis and Optimization of Renewable Energy Forecasting at Universitas Jenderal Achmad Yani - Handoko Rusiana Iskandar; Azhar Nurfatah; Ahmad Daelami; Een Taryana (ELECTRON Jurnal Ilmiah Teknik Elektro, 2023)
The availability of electrical energy ensures operational sustainability in everyday life, including the educational environment. The possibility of easier renewable energy installation encourages the goal of growing the installation to be affordable. Universitas Jenderal Achmad Yani is one of the campuses that has the capacity to use renewable energy and has a role in environmental awareness in accordance with the university's future vision. In light of this, a hybrid photovoltaic (PV), diesel, and battery plant design is presented as an alternative power plant to supplement conventional energy sources. However, it is critical to examine the long-term capital and profit estimations that must be considered. The hybrid plant is proposed in two configurations, grid-connected and off-grid. In this paper, modeling and simulation are performed using Net Present Cost (NPC) prices from the Ministry of Energy and Mineral Resources (MEMR) rooftop PV installation planning guidelines and inflation estimations from the Republic of Indonesia's Ministry of Finance. Furthermore, until the contribution of energy generated in the simulation is displayed, the production and consumption of electrical energy required for the selected building instances are generated. Hybrid plant modeling has been completed at Universitas Jenderal Achmad Yani’s Faculty of Health Sciences and Technology (FHST) and Rectorate buildings. According to the simulation results, the NPC cost for the next 25 years is anticipated to be Rp 1,047,534,000, with a total electrical energy production of 729,807 kWh/year and a renewable energy contribution >91.4%. Furthermore, from a technological and economic standpoint, a grid-connected hybrid generation system is advocated